PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN ONLINE CONSUMER REVIEW (OCR) TERHADAP KEPUTUSAN PEMBELIAN MELALUI SHOPEE - Sari, Indah; rinawati, tri; rizkiana, citra (Fakultas Ekonomi, Universitas Semarang, 2022)
This research aims to determine and analysis the influence of the Electronic Word of Mouth and Online Consumer Review on purchasing decisions through Shopee. This type of research is a quatitative descriptive research. The population in this study is students of University Semarang, internet users via marketplace Shopee, with a sample of 96 respondents. The study was done through a survey of Semarang University Student who made transactions through a Shopee and were analyzed with analysis regression. The results of the analysis show that Electronic Word of Mouth and Online Consumer Review has a positive and significant effect on purchase decisions through Shopee.